2011
DOI: 10.3109/01480545.2011.627863
|View full text |Cite
|
Sign up to set email alerts
|

Effects of granulocyte colony-stimulating factor on electrocardiogram changes after carbon monoxide poisoning in rats

Abstract: Carbon monoxide (CO), which is produced by the incomplete combustion of hydrocarbons, has many toxic effects on different organs, especially the brain and heart. CO-induced cardiotoxicity leads to several deleterious effects, including electrocardiogram (ECG) abnormalities. The present study aimed to evaluate the protective effect of recombinant human granulocyte colony-stimulation factor (G-CSF) on ECG after CO poisoning in rats. Single and multiple doses of G-CSF (10, 50, and 100 µg/kg) were administered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In previous studies, it was shown that by measurement of COHb levels in the blood of the exposed animals, we can confirm the induction of CO poisoning (Ghorbani et al , ; Mohamadpour et al , ). Our results showed that exposure to CO 3000 ppm for 1 h leads to a COHb level of 75 ± 9 ppm which confirmed CO intoxication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it was shown that by measurement of COHb levels in the blood of the exposed animals, we can confirm the induction of CO poisoning (Ghorbani et al , ; Mohamadpour et al , ). Our results showed that exposure to CO 3000 ppm for 1 h leads to a COHb level of 75 ± 9 ppm which confirmed CO intoxication.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that RES could ameliorate CO‐induced cardiovascular effects in an animal model (Hashemzaei et al , ). In order to find new substances that can fight the deleterious effects of CO poisoning in the heart and brain and also to shed light on the underlying mechanisms, in our previous studies, we discussed the involved pathways (Ghorbani et al , ; Hashemzaei et al , ; Mohamadpour et al , ). To the best of our knowledge, it is for the first time that the neuroprotective effect of multiple‐dose RES administration on CO poisoning is evaluated in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECG in lead I was recorded using PowerLab (ADInstruments, Bella Vista, New South Wales, Australia) before, during, and after CO poisoning. The ECG was analyzed with special focus on ST segment, T wave, atrioventricular (AV) block type 1 and 2, Q wave, premature ventricular contraction (PVC), sick sinus syndrome, ventricular tachycardia and fibrillation and atrial fibrillation ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite considerable advances in poisoning management, CO is still the leading cause of unintentional poisoning worldwide ( 5 6 ). CO is a colorless, odorless, tasteless and non-irritating gas which exerts its deleterious effects mostly in the organs with high oxygen demand including the brain and heart ( 5 7 8 ). Despite advances in toxicology, CO poisoning management has not been markedly changed over the last 100 years and still employs normobaric and hyperbaric oxygen along with symptomatic therapy ( 7 ).…”
Section: Introductionmentioning
confidence: 99%